The Management of the Gambus El-Hubb Music Group in Madiun Regency: Manajemen Grup Musik Gambus El-Hubb di Kabupaten Madiun - Oktavia Sari, Devy Indah; Rahayu,M.Hum, Dr. Eko Wahyuni (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
Abstract: The Gambus El-Hubb music group in Madiun Regency has been established since January 16 2016. The existence of the Gambus El-Hubb music group has received attention from the public and several institutions in Madiun Regency. The music group Gambus El-Hubb has an attraction with the characteristics of the group. This research aims to describe the management stages of the Gambus El-Hubb music group in Madiun Regency, as well as describe the obstacles and solutions for the Gambus El-Hubb music group in Madiun Regency. The method used in this research is qualitative research, because the data obtained and presented will be in descriptive form. Data sources are obtained from several data presented by sources, as well as other information, and in the form of documents. Data collection techniques were carried out using observation, interviews and documentation studies. Data validity is carried out using triangulation or merging techniques and comparing the data results obtained. The data analysis technique goes through the stages of data reduction, data presentation, and drawing conclusions. Based on the research results obtained, the management of the Gambus El-Hubb music group includes elements of well-organized management, and carries out management functions effectively and efficiently. However, there are several management practices that must be improved. Obstacles and solutions, obstacles that must be corrected by managing several unstructured group management. The solution for the Gambus El-Hubb music group is to maintain group management and create a more structured work program. Keywords: Management, Group, Gambus El-Hubb Music Abstrak: Grup musik Gambus El-Hubb di Kabupaten Madiun telah berdiri sejak 16 Januari 2016. Keberadaan grup musik Gambus El-Hubb mendapat perhatian dari masyarakat maupun beberapa lembaga yang berada di Kabupaten Madiun. Grup musik Gambus El-Hubb memiliki daya Tarik dengan memiliki ciri khas grup. Penelitian ini bertujuan untuk mendeskripskan tahapan manajemen grup musik Gambus El-Hubb di Kabupaten Madiun, serta mendeskripsikan kendala dan solusi grup musik Gambus El-Hubb di Kabupaten Madiun. Metode yang digunakan dalam penelitian ini adalah jenis penelitian kualitatif, karena data yang diperoleh dan dipaparkan akan berbentuk deskriptif. Sumber data diperoleh dari beberapa data yang dipaparkan oleh narasumber, serta informasi lain, dan berupa dokumen. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan studi dokumentasi. Validitas data dilakukan dengan teknik triangulasi atau penggabungan dan membandingkan hasil data yang diperoleh. Teknik analisis data melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil penelitian yang diperoleh pengelolaan manajemen grup musik Gambus El-Hubb meliputi unsur-unsur manajemen yang terorganisir dengan baik , dan menjalankan fungsi manajemen yang efektif dan efesien. Namun, ada beberapa pengelolaan manajemen yang harus diperbaiki. Kendala dan solusi, kendala yang harus diperbaiki dengan mengelola beberapa manajemen grup yang belum terstruktur. Solusi grup musik Gambus El-Hubb dengan mempertahankan dalam pengelolaan manajemen grup dan membuat program kerja yang lebih terstruktur. Kata kunci: Manajemen, Grup, Musik Gambus El-Hubb